2015
DOI: 10.4067/s0718-58392015000500001
|View full text |Cite
|
Sign up to set email alerts
|

Insights into rootstock biology under low oxygen

Abstract: Genetic characterization of lentil (Lens culinaris Medik.) cultivars is important for lentil breeding. Therefore, random amplified polymorphic DNA (RAPD) and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis were carried out to evaluate genetic diversity in 13 Turkish lentil cultivars. A total of eight RAPD primers were used in this study; 61 bands were produced and 55 of them were polymorphic (89.78%). The RAPD primers OPA-10, OPB-11, and OPI-13 had the highest polymorphism ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Traditional breeding efforts have made impressive progress towards improving rootstock performance in numerous plant species, but continued improvement remains limited to selection of existing traits within the gene pool of rootstock cultivars (Cousins, ). Hybridization breeding is also limited, as some elite traits may be lost in the process (van Nocker and Gardiner, ; Pinto, ). Progeny production, through sexual crossing and subsequent selection, is a lengthy and labour‐intensive process that can take a decade to reach fruition.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional breeding efforts have made impressive progress towards improving rootstock performance in numerous plant species, but continued improvement remains limited to selection of existing traits within the gene pool of rootstock cultivars (Cousins, ). Hybridization breeding is also limited, as some elite traits may be lost in the process (van Nocker and Gardiner, ; Pinto, ). Progeny production, through sexual crossing and subsequent selection, is a lengthy and labour‐intensive process that can take a decade to reach fruition.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al (2018) reported that band patterns obtained from the 14 lentil cultivars and 23 polypeptide bands were detected and from Sultana and Ghafoor (2008). They recorded 55 protein bands in lentils ranging from the molecular mass of 14 to 66 kDa, and 13 of these were polymorphic, and Erdogan (2015) reported that band patterns were obtained from the 13 lentil cultivars, and a total of 22 polypeptide bands were detected. Therefore, our results are similar to those of the authors (Kumar et al 2018).…”
Section: Discussionmentioning
confidence: 99%